The posterior hypothalamic area as an independent generator of rhythmic theta oscillatory activity - Pszczółkowska, Klaudia; Kowalczyk, Tomasz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2024)
Theta rhythm is one of the most prominent examples of rhythmic oscillatory activity in mammalian brain and it is generated mainly in structures of the limbic cortex, including the hippocampal formation. In the 1970s it was shown that theta rhythm may be also recorded in diencephalic region including the posterior hypothalamic nuclei and supramammillary nucleus, together considered as the posterior hypothalamic area (PHa). For decades it was stated that local posterior hypothalamic oscillatory activity is controlled by the descending inputs going to the PHa from the septohippocampal system. However, the latest studies indicated that theta rhythm can be recorded in deafferented PHa in vitro preparations which indicates that the posterior hypothalamic area should be considered as an independent of the other brain structures theta generator. In subsequent research the neurochemical and cellular basis of PHa theta were examined in both in vivo and in vitro conditions. In the light of multiple evidence obtained in these studies, it is the author’s intent to summarize the data concerning the role of the posterior hypothalamic area in hippocampal theta rhythm generation as well as the ability of that brain structure to independently generate theta rhythmicity.